Production and Marketing of Fruits and Vegetables in Karnataka : A Case Study of HOPCOMS - Seetha Naik, D.; Shivaraj, B. (Indian Journal of Marketing, 2006)
Fruits and vegetables are important basic necessities of life. The various kinds of vegetables differ in their nutrient values. Fresh and processed vegetables are high in minerals and vitamins. The use of vegetables as food is increasing over the decades. The quality of human life is also affected by the availability of fruits and vegetables at a reasonable price.The Government of Karnataka has created a society in an attempt to organize fruits and vegetables producers so that they gain economic strength in marketing their produce and earning remunerative prices for the same. The Horticultural Producers Cooperative Marketing Society Limited (HOPCOMS), Bangalore is a pioneering society in marketing of fruits and vegetables (F&V). This society was established in 1959 and this society is presently operating in nine districts of Karnataka and also only Karnataka has this type of operations in India.